2018
DOI: 10.33578/pjr.v2i6.6543
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kecanduan Siswa Terhadap Game Online (Studi Tentang Kebiasaan Siswa Bermain Game Online) Di SMP N 3 Teluk Kuantan

Abstract: The type of research used is qualitative research using field research types, the subjects in the study were students of SMP N 3Teluk Kuantan. While the method of data collection uses observation and interview techniques to obtain the information needed,then analyzed and described in written form. The results of this study indicate that the effects that arise due to addiction playonline games for students who are addicted including: 1) more time spent at the computer or internet cafe with a longerduration. 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…An online game-addicted teenager is more interested in an online game than any other activity [38]. This notion is similar to Edrizal's [27] findings, which state that online game addictions have negative impacts, such as spending more time playing games on a computer or in the Internet cafe, so someone might skip studying or other activities that can harm their health. A study also discovered that when the behavior of playing online games is repeated and normalized, the dopaminergic pathways in the brain will be stronger and persist, thus causing addiction, which will then strengthen the reactive system and weaken the reflective system.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…An online game-addicted teenager is more interested in an online game than any other activity [38]. This notion is similar to Edrizal's [27] findings, which state that online game addictions have negative impacts, such as spending more time playing games on a computer or in the Internet cafe, so someone might skip studying or other activities that can harm their health. A study also discovered that when the behavior of playing online games is repeated and normalized, the dopaminergic pathways in the brain will be stronger and persist, thus causing addiction, which will then strengthen the reactive system and weaken the reflective system.…”
Section: Discussionmentioning
confidence: 54%
“…A game is an activity that makes people feel happy and comforted [2]; therefore, it is undeniable that playing games can make someone eager to play regardless of the time of day. However, playing games every day can lead to addiction [26], [27]. In addition to characterizing games as hobbies, all informants had regularly played games for more than 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Then there are some participants who find it difficult to change because they are used to habits that are often done. Edrizal's [63] research found that one of the effects that emerged was less attention to health conditions, Kuss [64], said that online game addiction can trigger changes in activity and structure in brain areas related to motivation, memory, and control, Then Bass [65], revealed that the habit of playing online games is accompanied by an increase in dopamine levels in the dorsal striatum, then the dopamine pathway is investigated and encourages motivation to want to play more. In addition, playing games can cause cognitive abilities and self-control to decline.…”
Section: Discussionmentioning
confidence: 99%
“…Terlihat bahwa siswa candu sekali dengan game online ini. Menurut pendapat (Edrizal, 2018) siswa sekolah dasar saat bermain game online bisa menjadi lalai terhadap kehidupan sosial siswa sebab game online bisa menarik siswa hingga mereka tidak dapat terlepas dari handphone. Siswa lebih suka berinteraksi dengan teman mereka di dalam game online atau dunia maya dari pada berinteraksi dalam dunia nyata, terlalu lamanya bermain game online membuat siswa lupa akan kehidupan sosialnya.…”
Section: Hasil Dan Pembahasanunclassified